Reducing reject cotter valve skyrocketing cylinder head parts in retainer Press Machine Process in the automotive industry - Rosyidi, Edwar; Wibisono, Aprianto; Setiawan, Rohmat; Sugihartanti, Noviani Putri; Siregar, Januar Parlaungan; Pratama, Hafiidz Satria (Operations Excellence: Journal of Applied Industrial Engineering, 2025)
The automotive industry is an automotive company that produces various types of motorcycles, such as automatic, sport and cub. One of the processes is machining. This process is very important because quality is highly considered. In the machining process, the products produced are crankcase R, crankcase L, cylinder comp, cylinder head, crankshaft. Based on initial observations, this process found reject goods. In the cylinder head line machining area, especially the retainer press machine, there is a problem of reject cotter valve soaring and resulting in the repair process. This will have an impact on the addition of time to repair and product quality is reduced. PT XYZ is facing a problem with cotter valve soaring on the cylinder head product with daily report data for the last 3 months, the percentage of cotter valve soaring problems reaching 1.5% exceeding the maximum defect target of 0.5%. This study aims to reduce the level of reject cotter valve soaring during the retainer press machine pressing process. The method used is eight steps. One solution is to modify the punch size to adjust the urethane punch to work optimally. This process will have an impact on reducing the number of rejects. In addition, this repair also does not cause a repair process on the cylinder head part. The results of this study are very significant with the reduction in cotter cases soaring to 0.2%